The Experience of Using Dating Applications for Sexual Hook-Ups: A Qualitative Exploration among HIV-Negative Men Who Have Sex With Men in Hong Kong. Issue 6 (24th July 2021) - Choi, Kitty W. Y.; Choi, Edmond P. H.; Chow, Eric P. F.; Wan, Eric Y. F.; Wong, William C. W.; Wong, Janet Y. H.; Fong, Daniel Y. T.
ABSTRACT: Men who have sex with men (MSM) use dating applications (apps) to explore various romantic and sexual relationships. This qualitative study aimed to describe HIV-negative MSM's experiences with app usage, the sexual activities arranged accordingly and their experiences in using dating apps to arrange sexual encounters. Thirty-one MSM who were sexually active and who used dating apps were recruited. Individual semi-structured interviews were conducted. Qualitative data were thematically analyzed to outline significant phenomena and perceptions. The factors associated with matching on apps included sex roles, human immunodeficiency virus serostatus and availability of a venue for meetup. Facilitated by these apps, diverse types of sexual encounters were arranged. Condoms were typically used for safer intercourse, except by people who were younger and inexperienced or when drugs were consumed before or during sex (chemsex). Extensive interest in non-penetrative sexual behaviors was expressed by our sample. Searching for post-exposure prophylaxis methods and/or sexual health screenings was common after exposure to risk of infections. Sexually abusive encounters were followed by changes in sex-searching habits and lowered trust in relationship formation. The results of this study are important for the development of appropriate interventions to promote safer sexual practices among HIV-negative MSM dating app users.